2012
DOI: 10.1590/s1516-44462012000500005
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and joint hypermobility association: a systematic review

Abstract: Future research in large samples from the community and clinical setting and longitudinal studies of the association between anxiety and HA and the underlying biological mechanisms involved in this association are welcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Individuals with joint hypermobility often present autonomic abnormalities and stress-sensitive illnesses, including fibromyalgia, temporomandibular joint disorder and chronic fatigue syndrome (Smith et al, 2014 ). The strong link between anxiety disorder and joint hypermobility was first established in 1988 (Bulbena et al) and this finding has been widely replicated, confirming that joint hypermobility is associated with the heightened expression of anxiety symptoms (Garcia-Campayo et al, 2011 ; Bianchi Sanches et al, 2012 ; Smith et al, 2014 ) and represents a risk factor trait for developing anxiety disorders (Bulbena et al, 2011 ). However, little is known about the underlying neural mechanisms through which joint hypermobility and anxiety symptoms interrelate.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Individuals with joint hypermobility often present autonomic abnormalities and stress-sensitive illnesses, including fibromyalgia, temporomandibular joint disorder and chronic fatigue syndrome (Smith et al, 2014 ). The strong link between anxiety disorder and joint hypermobility was first established in 1988 (Bulbena et al) and this finding has been widely replicated, confirming that joint hypermobility is associated with the heightened expression of anxiety symptoms (Garcia-Campayo et al, 2011 ; Bianchi Sanches et al, 2012 ; Smith et al, 2014 ) and represents a risk factor trait for developing anxiety disorders (Bulbena et al, 2011 ). However, little is known about the underlying neural mechanisms through which joint hypermobility and anxiety symptoms interrelate.…”
Section: Introductionmentioning
confidence: 84%
“…Hypermobile participants experienced significantly higher state anxiety than the non-hypermobile participants. The association between joint hypermobility and the clinical expression of anxiety is now robustly established (Bulbena et al, 2011 ; Bianchi Sanches et al, 2012 ). In our non-clinical sample, hypermobile individuals demonstrated higher interoceptive accuracy when performing the heart beat detection task.…”
Section: Discussionmentioning
confidence: 99%
“…3% of the studied sample has JHS, with a 78% of sensitivity compared to the criteria of Hospital del Mar. Previous studies have shown a 10-20% prevalence of hypermobility affection in general population and a 60%-70% of JHS in patients suffering from panic/phobia cluster 1,2,5,6 . Recently a longitudinal study concluded that JHS is a risk factor for developing anxiety disorders, showing that patients with JHS present a higher incidence (RR: 22.6) of anxiety disorders than non JHS patients 13 .…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, a study conducted with brain magnetic resonance imaging (MRI) techniques observed structural differences in emotional-processing brain regions and specifically concluded that bilateral amygdala volume distinguished those participants with from those without hypermobility 14 . On the bases of these findings, the target sample of the study was deliberately chosen from an anxiety unit in order to detect more hypermobility subjects; therefore the percentage obtained was higher than in the general population but lower than the one proposed in studies that used an anxious clinical sample 5,6 . The observed difference with other anxious clinical samples might be due to the fact that 10% of our sample includes anxiety diagnosed spectrum disorders (obsessive-compulsive disorders, non-specified anxiety disorder and generalised anxiety disorder) but not panic/ phobic cluster which is described to be the most associated to joint hypermobility syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation